Brain MR Imaging Findings of Cardiac-Type Fabry Disease with an IVS4+919G>A Mutation - Lee, H.-J.; Hung, S.-C.; Hsu, T.-R.; Ko, S.-C.; Chui-Mei, T.; Huang, C.-C.; Niu, D.-M.; Lin, C.-P. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: A high incidence of cardiac-type Fabry disease with an α-galactosidase A mutation, IVS4 + 919 G>A, has been identified in the Taiwanese population. The neurologic manifestation has not been understood in this specific cardiac variant. This study aimed to investigate the typical imaging features of classic Fabry disease in patients with IVS4 Fabry disease.MATERIALS AND METHODS: Twenty-six patients with IVS4-type Fabry disease (20 men and 6 women; age range, 43–71 years; median age, 61 years) and 26 age- and sex-matched healthy controls (age range, 44–68 years; median age, 60 years) were analyzed for white matter hyperintensities, the pulvinar sign, and basilar artery diameter. The volumes of white matter hyperintensities were calculated by comparison with an in-house data base of 276 controls.RESULTS: Infarctions were found in 9 patients with IVS4 Fabry disease (35%) and in none of the healthy controls (P = .001). A pulvinar sign was found in 8 patients with IVS4 Fabry disease (30%) and in none of the healthy controls (P = .002). No significant difference was found in Fazekas scale scores for white matter hyperintensities; however, white matter hyperintensity volume in the deep white matter was higher in patients with IVS4 Fabry disease than in those from the healthy control data base (P = .004).CONCLUSIONS: Along with its involvement of the cardiac system, IVS4-type Fabry disease has features similar to those of classic Fabry disease and a higher frequency of deep white matter hyperintensities and a higher incidence of infarctions and pulvinar signs than in healthy controls.BAbasilar arteryGLAα-galactosidase AWMHwhite matter hyperintensity